Effects of isentropic efficiency of turbomachinery components on entropy production for small turbojet engine - Aygun, Hakan (Emerald Group Publishing Ltd, 2021)
Purpose Usage of gas turbine engines has increased by day due to rising demand for military and civil applications. This case results in investigating diverse topics related to energy efficiency and irreversibility of these systems. The purpose of this paper is to perform a detailed entropy assessment of turbojet engines for different flight conditions. Design/methodology/approach In this study, for small turbojet engines used in unmanned aerial vehicles, parametric cycle analysis is carried out at (sea level-zero Mach (hereinafter phase-I)) and (altitude of 9,000 m- Mach of 0.7 (hereinafter phase-II)). Based on this analysis, variation of performance and thermodynamic parameters with respect to change in isentropic efficiency of the compressor (CIE) and turbine (TIE) is examined at both phases. In this context, the examined ranges for CIE is between 0.78 and 0.88 whereas TIE is between 0.85 and 0.95. Findings Increasing isentropic efficiency decreases entropy production of the small turbojet engine. Moreover, the highest entropy production occurs in the combustor in the comparison of other components. Namely, it decreases from 2.81 to 2.69 kW/K at phase-I and decreases from 1.44 to 1.39 kW/K at phase-II owing to rising CIE. Practical implications It is thought that this study helps in understanding the relationship between entropy production and the efficiency of components. Namely, the approach used in the current analysis could help decision-makers or designers to determine the optimum value of design variables. Originality/value Due to rising isentropic efficiencies of both components, it is observed that specific fuel consumption (SFC) decreases whereas specific thrust (ST) increases. Also, the isentropic efficiency of a compressor affects relatively SFC and ST higher than that of the turbine.
Keywords: Turbojet; Specific entropy; Efficiency; Entropy production